On Islamic Concept of Man and Justice in Pancasila - al Hakim, Muhammad Hanif; Muhammad Maricar, Hudzaifah (Universitas Darussalam Gontor, 2023)
The issue of justice and fairness has been one of the hotly debated topics among mid-twentieth-century intellectuals following the independence of colonized countries. Indonesia, the country with the largest Muslim majority that proclaimed its independence at that time, had been practiced the ideals of a just and civilized humanity, which were enshrined in the second and fifth principles of Pancasila. After seven decades of independence, the gap between these noble ideals and the on-ground reality has widened. This article explores the concept of ‘justice’ in the second principle and ‘social justice’ in the fifth principle from an Islamic perspective. By utilizing the theory of justice proposed by Islamic intellectual figures, this research delves into the relationship between a just and civilized individual and social justice in the nation’s life in Indonesia. This is a library research employing a descriptive analytic method. The research shows that a just individual is one whose ‘nātiqah’ soul controls their ‘hayawaniyah’ soul. When this is achieved, the individual will possess the virtuous character required when holding strategic positions in governance. This virtuous character will guide them in formulating public policies, thus realizing social justice as outlined in the fifth principle of Pancasila.